2015
DOI: 10.1039/c4ta05194g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of titanium cross-linked chitosan composite for efficient adsorption and detoxification of hexavalent chromium from water

Abstract: For the simultaneous adsorption and detoxification of hexavalent chromium from water, a new titaniumchitosan (Ti-CTS) composite was synthesized through a metal-binding reaction between titanium ions and the chitosan biopolymer followed by cross-linking with glutaraldehyde. The resultant composite was characterized by FT-IR, XRD, elemental mapping, SEM and XPS. The adsorption properties toward Cr(VI) were systematically investigated as a function of pH, dosage, initial concentration, contact time, temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 41 publications
2
62
1
Order By: Relevance
“…Similar findings were reported by Habiba et al [48] and Archana et al [49], who stated that CS started to decompose at 200 • C, while CS-PVA-TiO 2 started to decompose at 250 • C. This behavior was attributed to the presence of TiO 2 . Moreover, Zhang et al [50] reported an increase in the glass transition temperature (Tg = 111.13 • C) and enthalpy (318.8 J/g) values in CS-whey protein film (104.46 • C and 258 J/g, respectively) by the incorporation of TiO 2 [48][49][50][51][52][53]. According to Vallejo-Montesinos et al [52] smaller amounts of TiO 2 may promote endothermic transitions to become a narrower composite, while higher amounts of TiO 2 may produce aggregates in the composite surface, which can affect their thermal stability [53].…”
Section: Chitosan-tio 2 (Cs-tio 2 ) Compositementioning
confidence: 99%
“…Similar findings were reported by Habiba et al [48] and Archana et al [49], who stated that CS started to decompose at 200 • C, while CS-PVA-TiO 2 started to decompose at 250 • C. This behavior was attributed to the presence of TiO 2 . Moreover, Zhang et al [50] reported an increase in the glass transition temperature (Tg = 111.13 • C) and enthalpy (318.8 J/g) values in CS-whey protein film (104.46 • C and 258 J/g, respectively) by the incorporation of TiO 2 [48][49][50][51][52][53]. According to Vallejo-Montesinos et al [52] smaller amounts of TiO 2 may promote endothermic transitions to become a narrower composite, while higher amounts of TiO 2 may produce aggregates in the composite surface, which can affect their thermal stability [53].…”
Section: Chitosan-tio 2 (Cs-tio 2 ) Compositementioning
confidence: 99%
“…Chitosan has a high positive charge density, which allows it to strongly interact with negatively charged dyes or metal ions [18][19][20][21]. A drawback of using chitosan is that it is soluble in acidic media (at pH < 6.0).…”
Section: Introductionmentioning
confidence: 99%
“…S15). S16), 47,48 verifying the guess. The presence of Cr(VI) species was confirmed by FT-IR spectroscopy.…”
Section: Cr(vi) Uptake Kinetics and Isothermmentioning
confidence: 79%